2023
DOI: 10.3390/nu15133052
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Osteoporosis Preventive Behaviors among Perimenopausal Women: A Cross-Sectional Study to Explore the Role of Knowledge and Health Beliefs

Abstract: Osteoporosis is a silent chronic disease, and many people did not discover it until they were diagnosed with a fracture. Therefore, regular scanning and appropriate Osteoporosis Preventive Behaviors (OPB) are the management cornerstone. OPB is strongly affected by personal knowledge and health beliefs. This study explores the role of knowledge and health beliefs as determinants of OPB among perimenopausal women. This cross-sectional study was performed on 1075 perimenopausal women in Najran City, Saudi Arabia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The positive effect of interventions on teachers [ 47 ] as well as combined programs (supplement consumption and physical activity) based on HBM [ 48 ] has been proven. Various studies have also confirmed the positive effect of HBM-based interventions [ 49 , 50 ] and the effect of multimodal interventions on reducing pain in the elderly [ 51 ]. The current study might provide similar findings.…”
Section: Discussionmentioning
confidence: 96%
“…The positive effect of interventions on teachers [ 47 ] as well as combined programs (supplement consumption and physical activity) based on HBM [ 48 ] has been proven. Various studies have also confirmed the positive effect of HBM-based interventions [ 49 , 50 ] and the effect of multimodal interventions on reducing pain in the elderly [ 51 ]. The current study might provide similar findings.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Elgzar et al found that knowledge and health beliefs related to osteoporosis were significantly associated with OPB among premenopausal women. They further added that perceived susceptibility, perceived seriousness, exercises’ perceived benefits, and health motivations are positive predictors of high OPB [ 16 ]. Finally, Blalock et al found knowledge and attitude as positive predictors for calcium and exercise among the premenopausal [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For coding, the right answer scored "1", and the wrong answer scored "0" The overall scale score ranges from 0 to 20, with a higher score demonstrating higher knowledge regarding osteoporosis. The total score of the participant was used to determine whether their knowledge was unsatisfactory (0-12) or satisfactory (13)(14)(15)(16)(17)(18)(19)(20). The Arabic version of OKAT had good internal consistency (r = 0.824) [29].…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total number of per menopausal women attending out-patients clinic of obstetrics department in Zagazig university hospital in six months are 300 women, high level of Osteoporosis Preventive Behaviors was 28.1% (Elgzar, et al 2023). With 95% confidence interval, 80% power of test.…”
Section: Sample Sizementioning
confidence: 97%